DAMPAK NILAI PERUSAHAAN AKIBAT PENGARUH MANAJEMEN PAJAK DAN LINDUNG NILAI TERHADAP KINERJA KEUANGAN - Basuki Toto Rahmanto; Mariah Mariah (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
The company carries out tax management and hedging strategies to improve the company's performance in increasing company value. This study aims to determine whether tax management and hedging have an effect on firm value by mediating financial performance variables. The use of mediating variables is expected to be a research novelty. The research population is banking sector companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling of banking companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. The statistical method used in this study is multiple linear regression analysis and path analysis. The results showed that tax management had no effect on financial performance, hedging had no effect on financial performance, tax management had no effect on firm value, hedging and financial performance had no effect on firm value, and tax management and hedging had no effect on firm value through financial performance Keywords: tax management, hedging, financial performance